Local Church and Livelihood Construction: Interlocking Social Domains and Evolving Scenarios of Synergy for Mission in Nyamira, Kenya - Ontita, Edward (Transformation, 2012)
Dominant Northern development expertise acknowledges religion mostly as impeding development processes and aim to secularize and ‘modernize’ the South. This paper seeks to map out the various intersections of church and actors’ livelihoods, and explain those nodal points through villagers’ eyes. The study employed ethnographic interviewing to weave life-histories of households, and analyzed data to locate patterns and concepts at intersections of church and livelihood. The paper reports that actors employed church as arena to construct, extend and defend livelihoods; and re-engineering a resource-system church is promising. Thus church interlocks with livelihood construction processes, presenting opportunities for synergy in mission.